The macrophage infectivity potentiator of Trypanosoma cruzi induces innate IFN-γ and TNF-α production by human neonatal and adult blood cells through TLR2/1 and TLR4 - Ait Djebbara, Sarra; Mcheik, Saria; Percier, Pauline; Segueni, Noria; Poncelet, Antoine; Truyens, Carine (Frontiers in Immunology, 2023)
We previously identified the macrophage infectivity potentiator of the protozoan parasite Trypanosoma cruzi (rTcMIP) as an immuno-stimulatory protein that induces the release of IFN-γ, CCL2 and CCL3 by human cord blood cells. These cytokines and chemokines are important to direct a type 1 adaptive immune response. rTcMIP also increased the Ab response and favored the production of the Th1-related isotype IgG2a in mouse models of neonatal vaccination, indicating that rTcMIP could be used as a vaccine adjuvant to enhance T and B cell responses. In the present study, we used cord and adult blood cells, and isolated NK cells and human monocytes to investigate the pathways and to decipher the mechanism of action of the recombinant rTcMIP. We found that rTcMIP engaged TLR1/2 and TLR4 independently of CD14 and activated the MyD88, but not the TRIF, pathway to induce IFN-γ production by IL-15-primed NK cells, and TNF-α secretion by monocytes and myeloid dendritic cells. Our results also indicated that TNF-α boosted IFN-γ expression. Though cord blood cells displayed lower responses than adult cells, our results allow to consider rTcMIP as a potential pro-type 1 adjuvant that might be associated to vaccines administered in early life or later.